Human Neutrophil-Mediated Nonoxidative Antifungal Activity against Cryptococcus neoformans - Mambula, Salamatu S. (American Society for Microbiology, 2000)
It has long been appreciated that polymorphonuclear leukocytes (PMN) kill Cryptococcus neoformans, at least in part via generation of fungicidal oxidants. The aim of this study was to examine the contribution of nonoxidative mechanisms to the inhibition and killing of C. neoformans. Treatment of human PMN with inhibitors and scavengers of respiratory burst oxidants only partially reversed anticryptococcal activity, suggesting that both oxidative and nonoxidative mechanisms were operative. To define the mediators of nonoxidative anticryptococcal activity, PMN were fractionated into cytoplasmic, primary (azurophil) granule, and secondary (specific) granule fractions. Incubation of C. neoformans with these fractions for 18 h resulted in percents inhibition of growth of 67.4 ± 3.4, 84.6 ± 4.4, and 29.2 ± 10.5 (mean ± standard error, n = 3), respectively. Anticryptococcal activity of the cytoplasmic fraction was abrogated by zinc and depletion of calprotectin. Antifungal activity of the primary granules was significantly reduced by pronase treatment, boiling, high ionic strength, and magnesium but not calcium. Fractionation of the primary granules by reverse phase high-pressure liquid chromatography on a C(4) column over an acetonitrile gradient revealed multiple peaks with anticryptococcal activity. Of these, peaks 1 and 6 had substantial fungistatic and fungicidal activity. Peak 1 was identified by acid-urea polyacrylamide gel electrophoresis (PAGE) and mass spectroscopy as human neutrophil proteins (defensins) 1 to 3. Analysis of peak 6 by sodium dodecyl sulfate-PAGE revealed multiple bands. Thus, human PMN have nonoxidative anticryptococcal activity residing principally in their cytoplasmic and primary granule fractions. Calprotectin mediates the cytoplasmic activity, whereas multiple proteins, including defensins, are responsible for activity of the primary granules.